The Influence Of Giving Education About Diarrhea On Mother Level Of Knowledge In Diarrhea Prevention In Children - Gevi Melliya (Journal of Nursing and Midwifery Sciences, 2023)
Diarrhea was a major disease killer in the age group of children. Diarrhea is transmitted by 4 factors, namely food (food), feces (feces), flies (air), and fingers (hands). Therefore, it was necessary to pay attention to the pattern of children's daily activities so that they do not endanger the child's health. Mothers play an important role in protecting and saving children from diarrhea armed with a good level of knowledge. Research Objectives: To determine the effect of providing education about diarrhea on the level of knowledge of mothers in preventing diarrhea in children. Methods: Quasy experimental design with one group pre-test post-test. The research sample was 60 respondents with a consecutive sampling technique. The instruments in the study were questionnaires and counseling programs regarding diarrhea. Statistical data analysis using the Wilcoxon Sign Rank Test analysis. The results of the mother's knowledge level in the pre-test category were enough for 27 respondents (45%) and the mother's level of knowledge most of the post-test in the good category as many as 47 respondents (78.3%), statistical test results show p-value 0.000 < α 0.05, it means that there is a significant influence between the provision of education about diarrhea on the level of knowledge of mothers in preventing diarrhea in children. live clean and healthy. Providing education about clean and healthy lifestyles and the understanding of diarrhea can be given to nurse mothers using both the lecture method and educational videos in reducing the incidence of diarrhea in children.